2002
DOI: 10.1097/00007890-200211150-00001
|View full text |Cite
|
Sign up to set email alerts
|

Successful A1-to-O ABO-incompatible kidney transplantation after a preconditioning regimen consisting of anti-CD20 monoclonal antibody infusions, splenectomy, and double-filtration plasmapheresis

Abstract: A preconditioning regimen consisting of rituximab infusions and a splenectomy is a useful new strategy for performing ABO-incompatible kidney transplantations when the conventional preconditioning regimen does not work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 9 publications
1
85
0
4
Order By: Relevance
“…However, all the evidence in humans was based on dosages of 375 mg/m 2 or over. Sawada et al reported that four doses of RIT at 375 mg/m 2 completely eliminated CD20 + B cells from the spleen in a renal transplant recipient [1]. Ramos et al showed that a single dose of RIT at 375 mg/m 2 , combined with plasmapheresis and intravenous immunoglobulin therapy, depleted most B cells, both CD20 + and CD79a + cells, from the spleen [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all the evidence in humans was based on dosages of 375 mg/m 2 or over. Sawada et al reported that four doses of RIT at 375 mg/m 2 completely eliminated CD20 + B cells from the spleen in a renal transplant recipient [1]. Ramos et al showed that a single dose of RIT at 375 mg/m 2 , combined with plasmapheresis and intravenous immunoglobulin therapy, depleted most B cells, both CD20 + and CD79a + cells, from the spleen [9].…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab (RIT; Chugai, Tokyo, Japan), a chimeric murine/human monoclonal antibody that binds to the CD20 antigen, has been employed as a component of desensitization protocols in renal transplant recipients, and for treatment of refractory rejection, which did not respond to initial treatment with high-dose steroids therapy, because of its potent B-cell elimination effect; the administration of RIT has provided excellent clinical outcomes [1][2][3][4][5][6]. Typically, a single dose of RIT at 375 mg/m 2 [2][3][4][5][6], which is known to lead to marked B-cell depletion in the peripheral blood and spleen [7][8][9], is administered instead of a splenectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for splenectomy as a strategy for AMR derives historically from its use in adjunctive desensitization protocols in kidney transplantation. [219][220][221][222][223] There are multiple reports of splenectomy as successful rescue therapy in a small number of patients with refractory AMR in kidney transplantation. 218,221,224 There are no reports, to the best of our knowledge, of splenectomy in heart transplant recipients with AMR.…”
Section: Splenectomymentioning
confidence: 99%
“…El mantenimiento de niveles bajos de isoagluti ninas durante el periodo temprano del postrasplante es críti co para la seguridad del injerto y en el caso del paciente se evidenció leve rebote de isoagluti ninas en el día 4 (IgG 4 a 16) asociado a incremento de niveles de creati nina (1,2 a 1,7 mg%) (36) . La mayoría de pérdidas de injertos por rechazo mediado por anti cuerpos ocurre en los tres primeros meses del post-Tx; por tanto es importante estar atentos al rebote de tí tulos de anti cuerpos anti -ABO en esta etapa (7,13,23,35) . En nuestro caso, no se desarrolló rechazo mediado por anti cuerpos a pesar del rebote (36) , y gracias a la aféresis postrasplante instaurada prontamente de tres recambios plasmáti cos fue benefi ciosa la evolución.…”
Section: Discussionunclassified